Implementing Sukuk Financing in Indonesia: Policy Actions to Improve and Support Development Research and Development Infrastructure (RDI) - Putera, Prakoso Bhairawa; Widianingsih, Ida; Rianto, Yan; Ningrum, Sinta; Suryanto, Suryanto (Research and Development Agency Ministry of Home Affairs, 2022)
The Indonesian government realizes that developing alternative instruments for financing the state budget needs to continue—one of them with financing instruments based on sharia principles. This study examines the response of the Indonesian government in policy actions to seek financing for research and development infrastructure through Sukuk financing. This study uses a qualitative method with a narrative approach. This study uses three data collection techniques: regulatory survey, secondary data research, and Expert Elicitation with Experts' Judgments. Meanwhile, the data analysis technique uses content analysis, stakeholder analysis matrix, 're-analysis,' and digital discourse analysis. The results of this research reveal that the policy actions taken by the Indonesian government are through 1) regulatory in the form of policies related to the Sukuk financing policy in Indonesia, by issuing one regulation in the form of a law, one rule in the form of a Government Regulation of the Republic of Indonesia, and four rules at the level of ministerial regulations. On the other hand, the results of the mapping of stakeholders show that there are four clusters of actors, namely decision makers, project initiators, support partners, and civil society - media. 2) applicative action in the form of budget allocation related to infrastructure financing Sukuk in the research and development sector, during 2018-2022, financed 41 projects from 10 ministries/agencies. In the end, this research provides recommendations; namely, it is necessary to diversify the types of infrastructure that can be financed from Sukuk financing so that they follow the needs of Ministries/Agencies and Local Governments.